The challenges of quantity surveying practice in sustainable construction project - Che Haron, Roziha; Ibrahim, Putri Haryati; Mat Rawi, Azya (2016)
Sustainable construction has led to changes in the complex environment of the construction industry. Globalisation has created to a new paradigm of sustainable practice resulting in growing demand for green construction and sustainable development. Nevertheless, since the understanding of sustainable construction in Malaysia is still in its infancy, quantity surveyors are struggling to respond to the green demand. This paper investigates the challenges facing quantity surveyors in managing green construction projects based on stages of project development. The findings show that quantity surveyors face numerous challenges brought by various factors during the management of these projects. This paper contributes to the body of knowledge of the green building environment by providing useful finding to serve as a reference for the stakeholders within the industry and the quantity surveyor specifically in entering green construction.